A two-stage strategy for methanogenesis suppression and rapid acetogenic biofilm formation in microbial electrosynthesis - Ferretti, Jacopo; Zegers, Marika A. J.; Zeppilli, Marco; Jourdin, Ludovic (Frontiers in Microbiology, 2025)
The practical implementation of microbial electrosynthesis (MES) is currently limited by the slow microbial colonisation of the electrode and the need to suppress methanogenic activity. This study investigates a two-stage strategy to suppress methanogenesis and promote the rapid formation of an acetogenic biofilm in a directed-flow-through bioelectrochemical reactor. Four start-up regimes were compared: mixotrophic without heat pre-treatment (M), mixotrophic with heat pre-treatment (MT), heterotrophic without heat pre-treatment (H), and heterotrophic with heat pre-treatment (HT), each followed by a common autotrophic phase. Mixotrophy outperformed heterotrophy by accelerating and increasing acetate accumulation. However, adding heat pre-treatment (MT) introduced a short lag phase and resulted in less sustained chain elongation than mixotrophy alone (M). Under the mixotrophic regime, microbial analysis showed an enrichment of genera with acetogenic representatives such as Clostridium sensu stricto 12 and Sporomusa, alongside a reduction in facultative anaerobic and fermentative bacteria. Full biofilm colonisation of the electrode was achieved within 55 to 65 days, while acetate, butyrate, and caproate production was initiated within the first week, reaching concentrations typically observed only after approximately 70 days under autotrophic conditions. Methane remained undetectable for about 40 days and, when detected later, exhibited low coulombic efficiencies (< 1%). Taken together, these results indicate that mixotrophic start-up provides a promising route to accelerate electrode colonisation and enhance early-stage productivity in MES, while highlighting the need for further optimisation and a deeper understanding of microbial interactions.